Digital Media and Human Rights Advocacy Against Sexual Violence: The Case of KemenPPPA’s Campaign in Indonesia - Kasyifa Alifya Anfasha; Dahlia Bunga Rembulan; Diffa Aulia Putri Syadena; Asmak Ul Hosnah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Sexual violence remains a pervasive human rights violation globally, with nearly one in three women experiencing physical or sexual abuse in their lifetime (UN Women, 2024). In Indonesia, the National Commmision on Violence against Women (Komnas Perempuan) reported 330,097 cases in 2024, of which 26,9% were sexual violence. Despite Law No. 12 of 2022 on the Crime of Sexual Violence (UU TPKS), gaps persist between legal enforcement and public awareness, emphasizing the need for effective advocacy. This study investigates the rol of digital media in human rights advocacy by analyzing KemenPPPA’s Instagram Reels campaign titled “Three Years Since the Enactment of the Sexual Violence Law.” Using a qualitative descriptive approach, data were collected through digital observation and documentation of the video, captions, and public comments. Framing Analysis (Entman, 1993) identified problem definitations, moral evaluations, and proposed solutions, while Normative Content Discourse Interpretation (NCDI) interpreted content based on national law and international human rights standards, particularly CEDAW. Findings show that the campaign communicates key human rights values, including victim protection, gender equality, and justice. The study highlights the potential of digital media as both an educational tool and platform for social participation, stressing participatory legal communication to complement formal law enforcement and advance women’s rights in Indonesia.